2020
DOI: 10.5194/tc-14-2581-2020
|View full text |Cite
|
Sign up to set email alerts
|

The ERA5-Land soil temperature bias in permafrost regions

Abstract: Abstract. ERA5-Land (ERA5L) is a reanalysis product derived by running the land component of ERA5 at increased resolution. This study evaluates ERA5L soil temperature in permafrost regions based on observations and published permafrost products. We find that ERA5L overestimates soil temperature in northern Canada and Alaska but underestimates it in mid–low latitudes, leading to an average bias of −0.08 ∘C. The warm bias of ERA5L soil is stronger in winter than in other seasons. As calculated from its soil temp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
75
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(76 citation statements)
references
References 59 publications
1
75
0
Order By: Relevance
“…While, in wider terms, we recommend the use of ERA5-Land fields over ERA5 for all types of land applications, one should factor in their choice elements such as available computer and data handling resources, importance of spatial resolution versus data volume, area of application, temporal consistency, etc. With the public release of ERA5-Land, research and development have already shown some caveats of the dataset, such as the treatment of soil temperature in permafrost regions (Cao et al, 2020). Further studies comparing with alternative well-referenced sites, as well as with regional and global datasets is encouraged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While, in wider terms, we recommend the use of ERA5-Land fields over ERA5 for all types of land applications, one should factor in their choice elements such as available computer and data handling resources, importance of spatial resolution versus data volume, area of application, temporal consistency, etc. With the public release of ERA5-Land, research and development have already shown some caveats of the dataset, such as the treatment of soil temperature in permafrost regions (Cao et al, 2020). Further studies comparing with alternative well-referenced sites, as well as with regional and global datasets is encouraged.…”
Section: Discussionmentioning
confidence: 99%
“…• (5600 m at the Equator) latitudelongitude climate modelling grid (CMG), for day and night overpasses Chen et al (2017). recommended the use of the MODIS LST average ensemble (i.e.…”
mentioning
confidence: 99%
“…ERA5-Land is still a new data set, and the few studies that have already documented some aspects of its performance (e.g. Cao et al, 2020;Pelosi et al, 2020) have not focused on northern Europe. In Fig.…”
Section: Era5-landmentioning
confidence: 99%
“…Thus, there are remaining uncertainties in temperature changes on the Tibetan Plateau. Given the Tibetan cryosphere's sensitivity to climate warming including frozen ground, accurate temperature records are crucial for gauging, for example, permafrost area extent decreases (Guo & Wang, 2013, active layer deepening (Peng et al, 2018), soil freeze depth decreases (Peng et al, 2017), the general decline in area extent of frozen ground (Guo & Wang, 2016), and soil temperature increases (Cao et al, 2020). been created at the global or regional scale, which have laid a solid foundation for an improved understanding of the overall changes in surface air temperature.…”
Section: Introductionmentioning
confidence: 99%